Clinical features, diagnosis and treatment outcomes of Cushing's disease in children: A multicenter study - Tarçın, Gürkan; Çatlı, Gönül; Çetinkaya, Semra; Eren, Erdal; Kardelen, Aslı Derya; Akıncı, Ayşehan; Böber, Ece; Kara, Cengiz; Yıldırım, Ruken; Er, Eren; Polat, Recep; Özhan, Bayram; et al. (Clinical endocrinology (Oxford), 2024)
Since Cushing's disease (CD) is less common in the paediatric age group than in adults, data on this subject are relatively limited in children. Herein, we aim to share the clinical, diagnostic and therapeutic features of paediatric CD cases. National, multicenter and retrospective study. All centres were asked to complete a form including questions regarding initial complaints, physical examination findings, diagnostic tests, treatment modalities and follow-up data of the children with CD between December 2015 and March 2017. Diagnostic tests of CD and tumour size. Thirty-four patients (M:F = 16:18) from 15 tertiary centres were enroled. The most frequent complaint and physical examination finding were rapid weight gain, and round face with plethora, respectively. Late-night serum cortisol level was the most sensitive test for the diagnosis of hypercortisolism and morning adrenocorticotropic hormone (ACTH) level to demonstrate the pituitary origin (100% and 96.8%, respectively). Adenoma was detected on magnetic resonance imaging (MRI) in 70.5% of the patients. Transsphenoidal adenomectomy (TSA) was the most preferred treatment (78.1%). At follow-up, 6 (24%) of the patients who underwent TSA were reoperated due to recurrence or surgical failure. Herein, national data of the clinical experience on paediatric CD have been presented. Our findings highlight that presenting complaints may be subtle in children, the sensitivities of the diagnostic tests are very variable and require a careful interpretation, and MRI fails to detect adenoma in approximately one-third of cases. Finally, clinicians should be aware of the recurrence of the disease during the follow-up after surgery.